'It's basically everywhere': young adults' perceptions of gambling advertising in the UK. (3rd December 2020) - Torrance, Jamie; Roderique-Davies, Gareth; Thomas, Samantha L; Davies, Nyle; John, Bev
Summary: In comparison to jurisdictions, such as Australia, limited research has focused upon the perceptions and reported effects of gambling advertising within the unique gambling environment of the UK. An online qualitative survey was conducted with 62 young adult gamblers in the UK. The survey investigated the place, meaning and influence of gambling advertising within the lives of the participants. Demographic data were analyzed using descriptive statistics, with qualitative data interpreted using inductive thematic analysis techniques. Three themes were identified. Firstly, young adults were highly cognizant of UK gambling advertising strategies. Second, young adults were able to describe the influence of gambling advertising including its normalizing effect and proliferation of misleading messages. Finally, young adults perceived that current harm minimization strategies, including responsible gambling messages, were ineffective. Many were supportive of increased regulation of gambling advertising. The findings indicate that young adults are aware of the potential risks associated with gambling advertising and are supportive of regulatory reform. It is important that the views and perspectives of young adults are fully considered by regulators and policy makers in the UK, particularly as they are a potential target demographic for the industry.